ANALISIS FAKTOR DETERMINAN YANG BERHUBUNGAN DENGAN KINERJA BIDAN DESA MENURUNKAN ANGKA KEMATIAN IBU DAN ANAK DI PUSKESMAS GUNUNGBARINGIN TAHUN 2021 - juwairiah hasibuan2 (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Health is a basic human right and is one of the factors that determine the quality of human resources. Midwives are one of the health workers who have an important and strategic position, especially in reducing maternal mortality, morbidity and infant mortality. Currently in the world the Maternal Mortality Rate (MMR) during childbirth and the Infant Mortality Rate, especially for newborns, is still high. The factors that influence the performance of midwives in documenting the MCH Handbook include knowledge, attitudes, skills, work motivation, compensation system, workload and work climate. Based on this, the role of the midwife as a service provider must be capable and skilled in providing services in accordance with the established standards. Midwifery services have a noble purpose, protecting and promoting women's health, especially helping pregnant women and their families. The services are provided so that women and their families gain emotional adjustment in dealing with pregnancy and childbirth, as well as ensuring that prospective mothers get sufficient knowledge, skills and information to enter the period of motherhood. These factors include factors related to the performance of village midwives in reducing maternal and child mortality at the Gunung Baringin Community Health Center. This research is a survey with a cross sectional research design. The total sample in this study was 42 midwives. Data were analyzed by Chi Square test with 0.05. The results of the study using bivariate analysis showed that there was a relationship between the knowledge of midwives and the performance of midwives with p value (0.002) < 0.05, there was a relationship between midwives' motivation and midwifery performance with p value (0.014) < 0.05, there was a relationship between midwife leadership and performance. midwife with p value (0.004) < 0.05, There is a relationship between midwife incentives and midwife performance with p value (0.014) < 0.05 and There is a relationship between midwife colleagues and midwife performance in reducing maternal and child mortality at Gunung Puskesmas Lay with p value (0.007) < 0.05. Keywords: Performance of Midwives, Mother and Child, and Puskesmas.